A FEMINISM READING IN NATHANIEL HAWTHORNEâS BIRTHMARK AND RAPPACINIâS DAUGHTER - Suhadi, Agung (LITERARY CRITICISM, 2015)
This paper investigates the effect of the prevailing patriarchal oppression towards female characters in Nathaniel Hawthorneâs short stories searching for identity through the lens of radical feminism, focusing specifically on authority and power. It can be seen that Hawthorne demonstrates how female characters struggle to define their lives as best as they can under male societal strictures in the early 19th century. The rationale is that by understanding the effect of dominant patriarchal culture in two tales of Nathaniel Hawthorne reveals the motivation towards the quest of identity among women of the period can be better understood. Hence, Hawthorneâs short stories serves as an indication and polemic of what happens to women when they are not allowed to attain their own identity independently of the men. Â This paper analyzes two famous short stories of Nathaniel Hawthorne namely Birthmark (1843) and Rappaciniâs Daughter (1844). The result of this research reveals that Hawthorne has challenged patriarchal oppression through âdeath as a triumphâ. In short, this research shows that Hawthorne in some ways exalts the rights of women to seek their own identity in society. Â Keywords : Female identity, radical feminism, patriarchal oppression, authority, power and Nathaniel Hawthorneâs tales